Photoresponse of supramolecular self-assembled networks on graphene–diamond interfaces - Sarah Wieghold (Nature Portfolio, 2016)
Two-dimensional, self-assembled heteromolecular networks often lack functionality. Here the authors study the photoresponse of self-assembled heteromolecular networks, while controlling their positions and interfaces at an atomic level, suggesting bottom-up assembly of optoelectronics devices.